The Coming Political Crisis in Afghanistan - Abdul Basit (2016)
The prevailing political deadlock and constitutional crisis in Afghanistan can be detrimental to the country's nascent democratic process. If a pragmatic solution through a fresh political agreement is not found, it will undermine the legitimacy of the National Unity Government (NUG).